PENGARUH TANAH EXISTING TERHADAP NILAI KUAT TEKAN BEBAS (UCS) PADA PERKERASAN LENTUR TIPE CEMENT TREATED’RECYCLING BASE (CTRB) - Suratno, Suratno; Radam, Iphan Fitrian; Yasruddin, Yasruddin (INFO-TEKNIK, 2023)
One alternative to repair damage to old road pavements is with recycling technology or recycling (CTRB) where Issues with the Mixed in Place procedure include mixing with pre-existing soil material, which should not be mixed during implementation as it will impact the Unconfined Compressive Strength (UCS) values. The Conch brand is less expensive as a binder than local cement from South Kalimantan since production expenses are lower.This study aims to determine the typical influence of existing soil on UCS, what percentage of existing soil material can still be tolerated either curing or non-curing, and correlation. It also aims to obtain recommendations for the maximum percentage of influence of percent of existing land on UCS in curing or non-curing. Finally, it aims to obtain UCS Results at minimal cement levels that still meet the requirements with the use of brand local cement. RAM samples were obtained for the purpose of investigation, which was done in a lab, existing soil and additional materials in the field. Inspection of old aggregates, making test specimens with variations in cement content of 1-10%, after obtaining minimum UCS according to technical requirements then making test specimens with variations in soil examinations and content UCS’ of 0%, 5%, 10%, 15%, 20%, and 25% again then conducting data analysis to find correlations / relationships. The results of the research showed variances in cement content of 1% (one) - 10% that still meet the technical specifications of UCS (at least 30 kg/cm²) obtained a minimum cement’ content of 5% (five percent) with a UCS of 33,77 kg/cm². Then the test results of the influence of existing soil on UCS that is still tolerated are mixed, namely in curing conditions is 17% with the equation Y = - 0.10075 x + 46.894 (R2 = 0,964). and non curing 8,9% with the equation Y = - 0,1113 x + 39,814(R2=0,956). The R2 conclusions for both indicate a very There is a substantial correlation between the two factors.